The teen birth. 3 study groups early, late adolescence and control group - Casas, Johnny (2015)
OBJECTIVE. To determine the influence of adolescence in maternal outcome. DESIGN. Adolescence was divided in early and late and compared with a control group 20 to 24 year-old. RESULTS. Incidence of deliveries in adolescent was 18,3%, 1,2% corresponding to early adolescence and 17,1% to late adolescence. Preeclampsia, eclampsia, threatened premature labor, anemia, and puerperal infection were significantly more frequent in early adolescence. There was lesspre-natal control, more premature labor and respiratory distress, and less infection in the newborn in early adolescence. There was no difference in results between late adolescence and control group. CONCLUSIÓN. Maternal and perinatal risks are more frequent in early adolescence.